Adipose mesenchymal stem cell-derived exosomes accelerate skin wound healing via the lncRNA H19/miR-19b/SOX9 axis - Qian, Li; Pi, Li; Fang, Bai-Rong; Meng, Xian-Xi (Laboratory investigation, 2021)
It has been reported that adipose mesenchymal stem cells (ADSCs) accelerate wound healing. Moreover, exosomes, which serve as paracrine factors, play a vital role in wound healing. However, the mechanism remains unclear. This research aimed to determine the roles of exosomes derived from ADSCs (ADSC-Exos) in wound skin tissue repair. Flow cytometry and electron microscopy were carried out to identify ADSCs and ADSC-Exos, respectively; RT-qPCR was performed to assess the lncRNA H19 (H19), microRNA19b (miR-19b) and SRY-related high-mobility-group box 9 (SOX9) levels; Western blotting was carried out to evaluate collagen and β-catenin expression; CCK-8, scratch and transwell assays were conducted to evaluate human skin fibroblast (HSF) cell proliferation, migration and invasion, respectively; the potential binding sites between H19 and miR-19b, miR-19b and SOX9 were detected by dual-luciferase reporter gene assay and RIP assay; and H&E staining was conducted to observe skin wound tissues. ADSC-Exos accelerated the proliferation, migration and invasion of HSF cells via H19. H19 acts as a molecular sponge towards miR-19b, which targets SOX9. ADSC-Exos inhibited miR-19b expression via H19, resulting in accelerated HSF proliferation, migration and invasion. ADSC-Exos upregulated SOX9 to activate the Wnt/β-catenin pathway, resulting in accelerated HSF cell proliferation, migration and invasion, and ADSC-Exos promoted skin wound healing via H19 in mice. The high expression of H19 in ADSC-Exos may upregulate SOX9 expression via miR-19b to accelerate wound healing of skin tissues. Our study may provide novel perspectives for therapy to accelerate skin wound healing. This study reveals that the long non-coding RNA H19 is highly expressed in exosomes derived from adipose mesenchymal stem cells and accelerates the proliferation, migration and invasion of human skin fibroblasts by upregulation of SOX9 and activation of the Wnt/β-catenin pathway The authors show that H19 affects SOX9 expression via the microRNA miR-19b to promote wound healing in injured skin.